Etiology of Severe Acute Hepatitis in a Pediatric Transplant Center in Japan. Issue 4 (31st March 2023) - Funaki, Takanori; Yamada, Masaki; Ide, Kentaro; Ito, Reiko; Shoji, Kensuke; Ogimi, Chikara; Imadome, Ken-Ichi; Kasahara, Mureo
Abstract: The proportion of pediatric cases with severe acute hepatitis of unknown etiology in the coronavirus disease 2019 era was higher than that in the pre-coronavirus disease 2019 era in Japan's largest pediatric transplant center. Further research and monitoring are essential.